EKSISTENSI DIGITAL DALAM MUSIK GEREJA REFLEKSI ALKITABIAH MAZMUR 40:4 - Setiawan, Eko Agus; Manalu, Nilawaty (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
Now, digital existence is moving faster and faster among the activities of billions of people. With it, each individual is integrated. On the other hand, digital concepts continue to transform and capture everyone's attention. Various literacies also discuss the good sides, challenges and opportunities of digital for humans and their generations. Added to this is the innovation of copying machines whose functions are not far from humans. It's called Artificial Intelligence (AI), a human-made intelligent machine designed to make human work easier. Finally, several opinions say that this machine will be a big threat if not managed properly. In this article the author will explain the existence of digital AI from a Christian perspective. Because like it or not, the church must accept and apply AI technology and media in its ministry to repair a broken world. However, modern technology will deny God's birth when it is in the wrong hands with the wrong motivation. David in his composition in (Psalm 40:4), reminds us that God is the creator of all good things for the glory of His name, not to destroy His creation. In another sense, digital was designed not for humanity's fall into sin, but instead for the work of salvation through the redemption He provided. In order to avoid misunderstandings about the existence of digitalization, the author will clarify the concept of digital in church music by providing a general overview of developing theories.